Odpowiedzi

2009-11-19T15:00:52+01:00
2009-11-19T15:11:19+01:00
A
3u + 2v = 2 ( mnożymy całość przez -2)
5u + 4v = 6
- 6u - 4v = - 4
5u + 4v = 6
dodajemy stronami
-6u + 5u - 4v + 4v = - 4 + 6
- u = 2
u = -2
5u + 4v = 6
5 razy - 2 + 4v = 6
- 10 + 4v = 6
4v = 16
v = 4
odp u = - 2 , v = 4
b
3s + 5t = - 6
1,5s - 2t = - 3 ( mnożymy całość przez - 2)
3s + 5t = - 6
- 3s + 4t = 6
dodajemy stronami
3s - 3s + 4t + 5t = - 6 + 6
9t = 0
t = 0
3s + 5t = - 6
3s + 0 = - 6
3s = - 6
s = - 6/3 = - 2
odp s = - 2 , t = 0
c
5 = 3x - y
5x - 2y = 7
3x - y = 5 ( mnożymy całość przez - 2)
5x - 2y = 7
- 6x + 2y = - 10
5x- 2y = 7
dodajemy stronami
- 6x + 5x + 2y - 2y = - 10 + 7
- x = - 3
x = 3
3x - y = 5
9 - y = 5
- y = 5 - 9
- y = - 4
y = 4
odp x = 3 , y = 4
d
x - 3y = 5( mnożymy przez - 3)
y + 3x = - 5
- 3x + 9y = -15
y + 3x = -5
dodajemy stronami
-3x + 3x + 9y + y = - 5 - 15
- 10y = - 20
y = 20/10 = 2
y + 3x = -5
2 + 3x = -5
3x = - 5 - 2
3x = -7
x = - 7/3
odp
x = -7/3
y = 2







  • Użytkownik Zadane
2009-11-19T15:12:21+01:00
A) 3u +2v=2
5u+4v=6

3u +2v=2/* (-2)
5u+4v=6

(-6u)-4v=(-4)
+ 5u+4v=6
podkreśl , a pod kreską
(-1u)=2/*-1

u= -2
3*(-2) +2v=2
(-6)+2v=2
2v=8/:2
V=4



b) 3s+5t=-6/*2
1,5s-2t=-3/*5

+ 6s+10t=-12
7,5s-10t=-15
podkreśl , a pod kreską
13,5s=-27/:13,5
S=-2
1,5*(-2)-2t=-3
-3-2t=-3
-2t=-3+3
-2t=0 równanie sprzeczne

c) 5=3x-y
5x-2y=7

3x-y=5/*-2
5x-2y=7

-6x+2y=-10
+ 5x-2y=7
podkreśl , a pod kreską
-x=-3/*-1
X=3
5=3*3-y
Y=9-5
Y=4


d) x-3y=5
y+3x=-5

x-3y=5
3x+y=-5/*3

+ x-3y=5
9x+3y=-15
podkreśl , a pod kreską
10x=-10/:10
X=-1


-1-3y=5
-3y=5+1
-3y=6/:-3
Y=-2